A left-sided incarcerated Amyand hernia in a 4-month-old male infant: a case report - Roya Golmoradi Pilehroud; Alireza Ziyabakhsh; Keyvan Amini; Reza Panahizadeh; Mohammadamin Vatankhah; Hamed Mohammadi Haris (Journal of Medical Case Reports)
Abstract Background Amyand hernias are inguinal hernias that involve the vermiform appendix and are very rare. Left-sided Amyand hernias are even rarer, and their diagnosis is often made intraoperatively. Case presentation In this article, we report a case of left-sided Amyand hernia in a 4-month-old Persian male infant. He presented with left groin swelling, which extended to his left scrotum. He had suffered from a reducible left-sided inguinal hernia since he was 3 months old, which was no longer reducible in this episode. The diagnosis of left-sided Amyand hernia was made intraoperatively, and appendectomy, cecum reduction, and herniorrhaphy were performed. Conclusion The best approach for treating Amyand hernias without appendicitis is controversial, and each approach has advantages and disadvantages; however, if there is acute appendicitis, appendectomy is recommended.